2015
DOI: 10.1002/ana.24389
|View full text |Cite
|
Sign up to set email alerts
|

Defective fast inactivation recovery of Nav1.4 in congenital myasthenic syndrome

Abstract: Objective To describe the unique phenotype and genetic findings in a 57-year-old female with a rare form of congenital myasthenic syndrome (CMS) associated with longstanding muscle fatigability, and to investigate the underlying pathophysiology. Methods We used whole-cell voltage clamping to compare the biophysical parameters of wild-type and Arg1457His-mutant Nav1.4. Results Clinical and neurophysiological evaluation revealed features consistent with CMS. Sequencing of candidate genes indicated no abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 52 publications
(114 reference statements)
1
74
0
2
Order By: Relevance
“…Recessive mutations of SCN4A causing loss of function have been associated with rare cases of congenital myasthenic syndrome [3,6]. Recessive mutations which completely abolish channel function were reported to cause a neonatal lethal condition, however the combination of full and partial loss of function mutations were associated with a classical congenital myopathy phenotype [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recessive mutations of SCN4A causing loss of function have been associated with rare cases of congenital myasthenic syndrome [3,6]. Recessive mutations which completely abolish channel function were reported to cause a neonatal lethal condition, however the combination of full and partial loss of function mutations were associated with a classical congenital myopathy phenotype [7].…”
Section: Discussionmentioning
confidence: 99%
“…These mutations in SCN4A can result in sustained muscle contraction, causing myotonia, or a prolonged refractory state with fast inactivation of the channel, yielding a periodic paralysis phenotype [4,5]. In rare cases recessive loss of function SCN4A mutations have been shown to cause a congenital myasthenic syndrome [3,6]. Recently, Zaharieva et al (2016) described a spectrum of phenotypes ranging from severe foetal hypokinesia to congenital myopathy, associated with loss of function of the channel due to recessive mutations in SCN4A in 11 patients from six unrelated families.…”
Section: Introductionmentioning
confidence: 99%
“…At a resting potential of −85 mV, greater than 90% of the mutant channels would be inactivated, thereby effectively causing haploinsufficiency and a 50% reduction of the Na + current. In the second reported case, the proband was homozygous for R1457H and heterozygous carriers in the family were asymptomatic (8). Expression studies in HEK cells revealed −15 mV left shift of inactivation and a 10-fold slower rate of recovery from inactivation.…”
Section: Sodium Channelopathies Of Musclementioning
confidence: 94%
“…Two families have been described for which de novo mutations of Na V 1.4 caused a myasthenic pattern of weakness (8, 260). Patients had generalized weakness during brief exercise, attacks of weakness involving the face and soft palate, and a decremental CMAP response during repetitive stimulation at 10 Hz and 50 Hz.…”
Section: Sodium Channelopathies Of Musclementioning
confidence: 99%
“…This combination of effects suggested a defect in muscle excitability downstream from the neuromuscular junction, and sequencing of SCN4A revealed a missense mutation in the voltage sensor of domain IV. Increased awareness that mutations of Na V 1.4 may occur in patients with symptomatic overlap between myasthenia and periodic paralysis led to the identification of additional isolated CMS cases, each of which was associated with recessive inheritance and homozygous missense mutations at arginines in the S4 of domain IV (Arnold et al, 2015; Habbout et al, 2016). …”
Section: Xx3 Overview Of Nav14 Mutationsmentioning
confidence: 99%